(untitled) (Research, Society and Development, 2021)
Sleep is an essential biological function of human beings related to quality of life, which can be assessed using scales such as the “Pittsburgh Sleep Quality Index”. Medical students are a population susceptible to poor sleep due to stress, academic obligations and other factors. Thus, the objective of this work was to gather information from the literature on the subject, in view of the growing relevance of the subject in the field of public health. This is an Integrative Literature Review that used descriptors in DeCS and the SciELO, BVS, LILACS and MEDLINE databases. Only studies that used the PSQI index were considered. The search in the databases initially resulted in 140 articles, after applying the exclusion and inclusion criteria, 18 articles were suitable for the final sample. Most articles (70%) showed poor sleep quality among students, but less than 15% had a sleep disorder. The mean of the available PSQI indices was 6.24 and the biggest factor associated with poor sleep quality were depression, anxiety, stress and higher scores for students with Irritable Bowel Syndrome. There is a need for educational strategies aimed at promoting health, including the adoption of healthier lifestyle habits such as physical activity, sleep hygiene and control of situations that induce awakening. Finally, more quality studies are needed to investigate risk factors for poor sleep quality in medical students.